2014
DOI: 10.1080/00071668.2013.879980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oregano and garlic essential oils on carcass characteristics, meat composition, colour, pH and sensory quality of broiler meat

Abstract: 1. An experiment was conducted to determine the individual and combined effects of two essential oils, oregano and garlic, on carcass characteristics, meat composition, colour, pH and sensory quality of broiler meat. 2. The diets were supplemented with no essential oil (control), oregano essential oil or garlic essential oil at 300 mg/kg and oregano essential oil at 150 mg/kg + garlic essential oil at 150 mg/kg. 3. Dietary oregano and garlic oil supplementation did not affect carcass yields, the relative weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
36
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 32 publications
16
36
2
2
Order By: Relevance
“…In the current study, the group treated with MOO had high values among slaughter variables, followed by control and oxytetracycline treatment groups (Table 5). Similar results were observed in hot carcass weight, cold carcass weight, hot carcass yield, and cold carcass yield by Mendez-Zamora et al (2015) and by Kırkpınar et al (2014) only on carcass yields.…”
Section: Resultssupporting
confidence: 77%
“…In the current study, the group treated with MOO had high values among slaughter variables, followed by control and oxytetracycline treatment groups (Table 5). Similar results were observed in hot carcass weight, cold carcass weight, hot carcass yield, and cold carcass yield by Mendez-Zamora et al (2015) and by Kırkpınar et al (2014) only on carcass yields.…”
Section: Resultssupporting
confidence: 77%
“…In contrast, Hong et al (2012) and Kırkpınar et al (2014) found no treatment differences for breast meat chemical compositions. This discrepancy could indicate that levels above 300 mg of OEO/kg of feed do influence protein and fat content.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, Küçükyılmaz et al (2014) found no differences in carcass yield, thighs, breasts, and wings when evaluating 28.8 mg of carvacrol/kg of feed over 81 days, but their results were higher than those of the current study. Kırkpınar et al (2014) found no influence on carcass yield, breasts, and thighs when evaluating 150 and 300 mg of OEO/kg in diets. Few studies have examined the effect of essential oils on cut piece yields and cooking loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These components exhibit antibacterial, antioxidant, antiviral, anti-fungal, and insecticide activities OrtegaNieblas et al, 2011). Recently, OEO was investigated in the production of chickens and turkeys (Gopi et al, 2013;Giannenas et al, 2014;Kirkpinar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%